Pengembangan LKPD Berdiferensiasi Berbantuan Canva Pada Mata Pelajaran IPAS Topik B Ragam Bentang Alam Daerahku Siswa Kelas IV Sekolah Dasar - Komang Krismayanti; Komang Surya Adnyana; I Ketut Ngurah Ardiawan (Prodi Pendidikan Guru Sekolah Dasar, 2025)
The goal of this project is to create a useful and valid learning resource for the Natural and Social Sciences course at grade IV Elementary Schools in Cluster III, Buleleng District, in the form of a Canva-assisted Differentiated Student Worksheet about the variety of natural landscapes in my area. The ADDIE model, which has five stages of development—analysis, design, development, implementation, and evaluation—is the methodology or model type employed in this work. In addition to using a questionnaire to gather information on the degree of validity of the learning materials, this study solely looks at the Development stage of the ADDIE model. Three experts—media experts, language experts, and material experts—completed this questionnaire. According to the study's findings, the Canva-assisted Differentiated Student Worksheet learning product scored 0.90 overall out of the three experts' evaluations. A questionnaire was employed with seven practitioners/grade IV teachers as responders during the practicality test phase. The practicum's outcomes had a very high validity statement and an average of 0.95. Based on these findings, the study and creation of distinct LKPD learning materials, with Canva's help, on the content of the diverse natural landscapes in my region for the Natural and Social Sciences course is deemed to be very legitimate, useful, and doable.